Comparison of volumetric and stress-weighted water footprint of grain products in China. (January 2015) - Wang, Y.B.; Wu, P.T.; Engel, B.A.; Sun, S.K.
Highlights: Volumetric WF and stress-weighted WF of each region in China differed greatly. There were differences of both kinds of WFs among different regions in China. Volumetric WF can be used as an indicator for evaluating water use efficiency. Stress-weighted WF provides water stress by human production or consumption. Abstract: The water footprint (WF) concept links physical and virtual forms of water, which can be used for research on the impact on water resources imposed by human consumption or production activities. Debates remain on the calculation methods due to WF being applied for different research purposes, and the large amounts of data required for the calculation being hard to obtain. This paper calculated and compared two WFs called volumetric WF (the volumes of blue and green water are combined with the same weight) and stress-weighted WF (the volumes of blue and green water are combined with different weights) based on water use data to research crop water productivity of grain crops and its impact on water resources in each region of China. Results for volumetric WF and stress-weighted WF of grain products of each region in China differed greatly. In 2010, the average volumetric WF was 1.25 m 3 /kg with the blue component 0.53 m 3 /kg, and the average stress-weighted WF was 0.51 m 3 /kg. In addition, there were significant differences of both kinds of WFs among regions in China. The results showed that volumetric WF could be used as a comprehensive indicator for evaluating crop water productivity, specified in space and time by source (green and blue WFs). Stress-weighted WF could offer a meaningful way of making quantitative comparisons between products, production systems and services in terms of their potential to contribute to water scarcity. The spatial distribution of these two WFs can help decision making to develop water-saving measures, relieve water stress and restore ecosystems for each region in China.